RUMAH LITERASI SEBAGAI SARANA ALTERNATIF PENUMBUHAN MINAT BACA SISWA SDN KANAAN: Artikel Pekan Kreativitas Mahasiswa Pengabdian Masyarakat - Rumah Literasi Sebagai Alternatif Penumbuhan Minat Baca SiswaÂ SDNÂ Kanaan - Ikartika, Ika; Haloho, Elisabet; Fifi Afriliya, Lynta; Rahman, Naufal; Ananta Wiguna, Tessa (Jurnal Difusi, 2024)
Literacy culture plays a vital role in the development of education in Indonesia, bringing a number of significant benefits to individuals and society. This service project emerged as a response to the low interest in reading, especially at SDN Kanaan, which is influenced by the lack of facilities, less attractive learning models, and limited programs and books that match students' interests. The purpose of this social project is to foster reading interest among students of SDN Kanaan to build a sustainable literacy culture. The literacy movement for students is the main focus of this activity, with the establishment of Rumah Literasi in an abandoned room as a concrete step. The hope is that the provision of adequate facilities can encourage students to make reading a passion or hobby, turn reading activities into fun experiences, and improve academic achievement. In the context of education in remote areas (3T), community service, especially the active role of students, is key in building a culture of literacy. Students act as agents of change by providing inspiration, motivation and support to improve children's literacy skills. Through collaborative and creative efforts, students can help create a learning environment that stimulates interest, understanding and love for reading and writing among children.